New generation of portal software and engineering : emerging technologies - Polgar, Jana, 1945-; Adamson, Greg. (Hershey, PA : Information Science Reference, 2011)
'This book presents a strong understanding of Portals, SOA, the published research in these fields, as well providing an enterprise-based experience of factors that challenge implementation of Portal and SOA projects in practice'--Provided by publisher.
'Premier reference source'--Cover.
Includes bibliographical references and index.
Keywords: Web portals; Service-oriented architecture (Computer science); Computer network architectures; Web site development; Web sites -- Design; Application software -- Development